Biogenic synthesis of silver nanoparticles from Cassia fistula (Linn.): In vitro assessment of their antioxidant, antimicrobial and cytotoxic activities. Issue 6 (1st December 2016) - Mohanta, Yugal Kishore; Panda, Sujogya Kumar; Biswas, Kunal; Tamang, Abiral; Bandyopadhyay, Jaya; De, Debashis; Mohanta, Dambarudhar; Bastia, Akshaya Kumar
Abstract : The present study reports on biogenic‐synthesised silver nanoparticles (AgNPs) derived by treating Ag ions with an extract of Cassia fistula leaf, a popular Indian medicinal plant found in natural habitation. The progress of biogenic synthesis was monitored time to time using a ultraviolet–visible spectroscopy. The effect of phytochemicals present in C. fistula including flavonoids, tannins, phenolic compounds and alkaloids on the homogeneous growth of AgNPs was investigated by Fourier‐transform infrared spectroscopy. The dynamic light scattering studies have revealed an average size and surface Zeta potential of the NPs as, −39.5 nm and −21.6 mV, respectively. The potential antibacterial and antifungal activities of the AgNPs were evaluated against Bacillus subtilis, Staphylococcus aureus, Candida kruseii and Trichophyton mentagrophytes . Moreover, their strong antioxidant capability was determined by radical scavenging methods (1, 1‐diphenyl‐2‐picryl‐hydrazil assay). Furthermore, the AgNPs displayed an effective cytotoxicity against A‐431 skin cancer cell line by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) assay, with the inhibitory concentration (IC50 ) predicted as, 92.2 ± 1.2 μg/ml. The biogenically derived AgNPs could find immense scope as antimicrobial, antioxidant and anticancer agents apart from their potential use in chemical sensors and translational medicine.